DIGITAL TRANSFORMATION IN ROMANIA'S AGRICULTURE IN THE PERIOD 2023-2027 - Daniel-George ȘERBAN; Emanuela LUNGU; Florina Loredana ȘERBAN; Maria Magdalena TUREK RAHOVEANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The influence of new technologies and digitalization in general on the agriculture sector is a topic of great discussion these days. Digitalization of agriculture and so-called precision farming appear to be the intended answers to a number of problems, like the need for higher output, the desire to become greener, or the declining population. The paper aims to analyze the influence of new technologies and digitization on the agricultural sector, focusing on the opportunities and challenges of precision agriculture. The study will examine how the digital transition can address the challenges of sustainable agricultural production, ecological impact, and human resource management, given the National Strategic Plans implemented by the EU through the post-2020 Common Agricultural Policy (CAP). The main results indicate that the digitization of agriculture has led to a significant increase in productivity (up to 20%), a reduction in the use of environmentally harmful resources (fertilizers and pesticides by 15%), but high initial costs and a lack of adequate infrastructure challenges small farmers over time that financial support and post-2020 CAP mechanisms are essential to accelerate the transition to precision agriculture.